2015
DOI: 10.5194/bg-12-6389-2015
|View full text |Cite
|
Sign up to set email alerts
|

C : N : P stoichiometry at the Bermuda Atlantic Time-series Study station in the North Atlantic Ocean

Abstract: Abstract. Nitrogen (N) and phosphorus (P) availability, in addition to other macro-and micronutrients, determine the strength of the ocean's carbon (C) uptake, and variation in the N : P ratio of inorganic nutrient pools is key to phytoplankton growth. A similarity between C : N : P ratios in the plankton biomass and deep-water nutrients was observed by Alfred C. Redfield around 80 years ago and suggested that biological processes in the surface ocean controlled deepocean chemistry. Recent studies have emphasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 68 publications
4
22
1
Order By: Relevance
“…The inorganic nutrients released form the mineralization of high N:P dissolved organic matter should accumulate at ratios higher that the Redfield value and contribute to the development of high N:P ratios (Hansell et al, ). The TON:TOP ratios found in the surface of NASW (231:1 ± 70) and the EDW waters (Figure h) exceed data of previous studies from the western subtropical Atlantic that report values of about 60–90:1 (Ammerman et al, ; Singh et al, ; Wu et al, ), while those found below the EDW and in the SSNA region (TON:TOP ≈ 50:1) agree. We think that a combination of all the previously stated factors: sedimentation of diazotrophs, sedimentation of N‐rich organic matter resulting from preferential surface P remineralization, and the horizontal transport and mineralization of high N:P dissolved organic matter within the EDW, converges to produce the high dissolved inorganic N:P ratios of the subsurface NASW.…”
Section: Discussionsupporting
confidence: 54%
“…The inorganic nutrients released form the mineralization of high N:P dissolved organic matter should accumulate at ratios higher that the Redfield value and contribute to the development of high N:P ratios (Hansell et al, ). The TON:TOP ratios found in the surface of NASW (231:1 ± 70) and the EDW waters (Figure h) exceed data of previous studies from the western subtropical Atlantic that report values of about 60–90:1 (Ammerman et al, ; Singh et al, ; Wu et al, ), while those found below the EDW and in the SSNA region (TON:TOP ≈ 50:1) agree. We think that a combination of all the previously stated factors: sedimentation of diazotrophs, sedimentation of N‐rich organic matter resulting from preferential surface P remineralization, and the horizontal transport and mineralization of high N:P dissolved organic matter within the EDW, converges to produce the high dissolved inorganic N:P ratios of the subsurface NASW.…”
Section: Discussionsupporting
confidence: 54%
“…). The higher Q C : Q N ratio in autotrophic biomass could significantly increase estimates of C export from the euphotic zone (Teng et al ., ; Singh et al ., ) and potentially help resolve C budgets in the ocean (Burd et al ., ). Additionally, a simple mass balance would imply that the remainder of particles making up organic matter in the North Atlantic Ocean must be relatively enriched in N. Presumably, this would be primarily due to heterotrophic bacterial cells, which potentially have a lower range of stoichiometric ratios (minimum Q C : Q N = 4) in marine systems (Gundersen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The oceanic residence times of N and phosphorus (P) are therefore quite distinctly different, despite their close ocean scale coupling as is evident from the Redfield ratio. This coupling is due to large‐scale thermohaline water mixing that smooths out the effects of the different internal ocean biogeochemical N and P cycling [ Martiny et al ., ; Singh et al ., ; Weber and Deutsch , ]…”
Section: Biological Nitrogen Fixationmentioning
confidence: 99%